COMMITMENT OF NAHDLATUL ULAMA AND MUHAMMADIYAH EDUCATION INSTITUTIONS IN BREAKING THE CHAIN OF RADICALISM - Ilham Tohari; Moh. Zainullah; Umar Faruq; Nada Oktavia (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2022)
This paper aims to identify the role of NU and Muhammadiyah educational institutions in preventing the potential for radicalism in Lamongan and Malang, which are well known as the basis of radicalism. In this research, the method used by the researcher is part of field research and uses a phenomenology perspective. The result of this research is that educational institutions have an essential role in breaking the chain of radicalism, as Nahdlatul Ulama educational institutions did with their aswaja values and Muhammadiyah with their al-Islam and Kemuhammadiyahan values. The existence of NU and Muhammadiyah can be the movement of tolerance in addressing diversity within the internal of Muslims or among other religions, which in their daily lives cannot be separated from various kinds of differences.